Testing for SARS-CoV-2 - Popadić, Dušan (Medicinski podmladak, 2021)
This review article describes the principles and implications of certain tests for diagnosing SARS-CoV-2 infections. The advantages and disadvantages of certain tests, both those in routine diagnostic application and those that have primarily research significance, are discussed. Also, a review of the practice of reporting results is given, as well as recommendations for its improvement.